1989
DOI: 10.1002/jcb.240400314
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activating factor (PAF) production by mouse embryos in vitro and its effect on embryonic metabolism

Abstract: Factors affecting the production of platelet activating factor (PAF) by mouse embryos during culture in vitro were investigated. Detectable levels of embryo-derived PAF were produced within 1-4 hr with maximum PAF activity being observed after 6 hr of culture in vitro. The amount of PAF detected in media after 24 hr of culture of two-cell embryos was equivalent to 12.8 ng PAF/embryo. However, differences in activity were apparent with increased time in culture. Reduced synthesis of PAF during culture in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Continuous culture of bovine embryos throughout preimplantation development in the presence of SOFaaBSA supplemented with 10 -20 mM PAF led to a significant increase in the utilisation of pyruvate and glucose but did not alter lactate production. These observations suggest an enhancement in oxidative metabolism, as reported by Ryan et al (1989Ryan et al ( , 1990b, who found a similar dosedependent enhancement of oxidative metabolism by murine blastocysts cultured in the presence of PAF, suggesting that PAF may induce the embryo to favour more energyefficient pathways. Furthermore, the data suggest that 10 mM PAF can, to some extent, 'rescue' embryos cultured $ 390 mm apart.…”
Section: That Highsupporting
confidence: 81%
See 2 more Smart Citations
“…Continuous culture of bovine embryos throughout preimplantation development in the presence of SOFaaBSA supplemented with 10 -20 mM PAF led to a significant increase in the utilisation of pyruvate and glucose but did not alter lactate production. These observations suggest an enhancement in oxidative metabolism, as reported by Ryan et al (1989Ryan et al ( , 1990b, who found a similar dosedependent enhancement of oxidative metabolism by murine blastocysts cultured in the presence of PAF, suggesting that PAF may induce the embryo to favour more energyefficient pathways. Furthermore, the data suggest that 10 mM PAF can, to some extent, 'rescue' embryos cultured $ 390 mm apart.…”
Section: That Highsupporting
confidence: 81%
“…Day-8 blastocyst (pmol/cell/h) (Roberts et al 1993) and blastocyst cell number (Stoddart et al 1996, O'Neill 1997 -increase the oxidative metabolism of glucose and lactate in the mouse (Ryan et al 1989(Ryan et al , 1990b. Expressing metabolism on a per cell basis revealed no significant effect of adjacent embryo distance.…”
Section: Day-8 Blastocyst (Pmol/embryo/h)mentioning
confidence: 98%
See 1 more Smart Citation
“…The binding of Paf to the platelet-activating factor receptor (PTAFR), a member of the G protein-coupled receptor family, accounts for many of the reported actions of Paf (Ishii et al 2002). Paf is produced and released by embryos during preimplantation development of all eutherian species studied to date: mouse (O'Neill 1985, Ryan et al 1989, Roudebush et al 2002, rabbit (Minhas et al 1993), sheep (Battye et al 1991), hamster (Velasquez et al 1995) and human (Collier et al 1990, Nakatsuka et al 1992. No embryos of marsupial species have yet been examined, although Paf appears to be produced by the endometrium of the tammar during the period of reactivation (Kojima et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, the addition of Paf can stimulate embryo metabolism (Ryan et al 1989(Ryan et al , 1990a, increase total cell number (Ryan et al 1990b, Roudebush et al 1996 and promote overall embryo development and viability (Nishi et al 1995, Stoddart et al 1996, O'Neill 1997, 1998. Furthermore, Paf has the critical function of generating a pro-survival antiapoptotic transcriptome within the embryo (Jin & O'Neill 2011) and has the net effect of maintaining the tumour suppressor protein p53 in a latent state (Jin et al 2009).…”
Section: Introductionmentioning
confidence: 99%